1995
DOI: 10.1136/bmj.311.6996.18
|View full text |Cite
|
Sign up to set email alerts
|

Stroke patients' views on their admission to hospital

Abstract: Patients have important psychosocial needs during the acute stage of the stroke, which are often met by hospital admission. Patients gained benefits from their admission over and above those measurable in terms of morbidity or function. They used a combination of criteria to evaluate their care, focusing on the process as well as the outcome of care. Researchers and clinicians should do likewise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 16 publications
1
55
0
Order By: Relevance
“…Backe et al (1996) reported that in the first week after stroke, patients' feelings of unreality and awareness of their changed role might lead to psychological crisis. 9 In retrospective studies, patients have been reported as appreciating the hospital care they received, valuing being cared about as well as being cared for, 37 and expressing high levels of satisfaction. 38 …”
Section: Acute Carementioning
confidence: 99%
“…Backe et al (1996) reported that in the first week after stroke, patients' feelings of unreality and awareness of their changed role might lead to psychological crisis. 9 In retrospective studies, patients have been reported as appreciating the hospital care they received, valuing being cared about as well as being cared for, 37 and expressing high levels of satisfaction. 38 …”
Section: Acute Carementioning
confidence: 99%
“…Patients in a study of stroke services in the United Kingdom reported high levels of satisfaction with inpatient care [4]. A substantial proportion of patients and their families also reported dissatisfaction with the lack of involvement in decisions [5]. A different patient journey study in the UK [6] showed that four main themes emerged from questioning patients and their families about their in-hospital experiences; (1) information provision, (2) staff attitudes, (3) availability of care, and (4) considering the whole person in context.…”
Section: Introductionmentioning
confidence: 99%
“…Research has found that information is considered by stroke survivors to be a vitally important component of care [35] , but in most cases individuals perceive gaps in the information they have received [36] . In other words, the DMSS Resource…”
Section: The Distress Management System For Stroke (Dmss)mentioning
confidence: 99%